Development of e-learning on lecture application (calculus) / Murni Jainaf - Jainaf, Murni (2003)
E-Learning is an internet-enable learning mechanism. It is a combination of computer hardware, software and the internet that can make learning simpler than the conventional learning approach [1]. This project is about developing an e-Learning application on calculus for Degree students. The system is designed using Visual Basic 6 Programming, Microsoft Access database program and Multimedia Interactive software. Through this system, lecturers and student can teach and learn calculus (MAT 582) interactively according to their pace and time.